Monitoring the psychological, social, and economic impact of the COVID‐19 pandemic in the population: Context, design and conduct of the longitudinal COVID‐19 psychological research consortium (C19PRC) study - McBride, Orla; Murphy, Jamie; Shevlin, Mark; Gibson‐Miller, Jilly; Hartman, Todd K.; Hyland, Philip; Levita, Liat; Mason, Liam; Martinez, Anton P.; McKay, Ryan; Stocks, Thomas VA; Bennett, Kate M.; et al. (International journal of methods in psychiatric research, 2021)
ABSTRACT Objectives The C19PRC study aims to assess the impact of the COVID‐19 pandemic in the adult population of the UK, Republic of Ireland, and Spain. This paper describes the conduct of the first two waves of the UK survey (the “parent” strand of the Consortium) during March–April 2020. Methods A longitudinal, internet panel survey was designed to assess: (1) COVID‐19 related knowledge, attitudes, and behaviors; (2) the occurrence of common mental health disorders as well as the role of (3) psychological factors and (4) social and political attitudes, in influencing the public's response to the pandemic. Quota sampling (age, sex, and household income) was used to recruit a nationally representative sample of adults. Results Two thousand and twenty five adults were recruited at baseline, and 1406 were followed‐up one‐month later (69.4% retention rate). The baseline sample was representative of the UK population in relation to economic activity, ethnicity, and household composition. Attrition was predicted by key socio‐demographic characteristics, and an inverse probability weighting procedure was employed to ensure the follow‐up sample was representative of the baseline sample. Conclusion The C19PRC study data has strong generalizability to facilitate and stimulate interdisciplinary research on important public health questions relating to the COVID‐19 pandemic.